Theoretical fluid dynamics - Shivamoggi, Bhimsen K (New Delhi, John wiley & sons, inc, 2014)
Complex Analysis is a fundamental branch of mathematics that has important applications in many areas of the physical sciences.
Bibliography 535-546p.; Subject index 547-555p.
Keywords: Dynamics turbulence; Fluid dynamics; Fluid flows; Mathematics